The Ethiopic ‘Andəmta’ Commentary on Ethiopic Enoch 2 (1 Enoch 6–9) - Lee, Ralph (Journal for the study of the pseudepigrapha, 2014)
The little-studied corpus of biblical commentary material in the Ethiopian Orthodox Church includes a commentary on the book of Enoch. The commentary tradition reflects the outlook of seventeenth-century Gondar, the then capital of Ethiopia, although it undoubtedly contains much older material. Enoch is an important book in the Ethiopian tradition, with its theology underpinning the interpretation of many other books. This article presents a translation of the commentary on Enoch 6–9, the fallen angels, and the related commentary on Ps. 82(81).7. The commentary views the fallen angels as holy men who fell into temptation, and reflects the strongly ascetic outlook of Ethiopian Christianity. The commentary on Psalm 82 includes reference to a story found in the Midrash ha-Gadol on Genesis raising the question of the influence of Jewish commentary material on the Ethiopian tradition.